2023
DOI: 10.3390/jcm12062264
|View full text |Cite
|
Sign up to set email alerts
|

Promising Perinatal Outcome after Using a Simplified Low-Cost IVF Culture System Specifically Designed for Resource-Poor Countries

Abstract: Background: Assisted reproductive techniques services are often not accessible to the majority of infertile couples in Low and Middle Income Countries (LMIC) due to high costs. Lowering IVF laboratory costs is a crucial step to make IVF affordable for a larger part of the world population. We developed a simplified culture system (SCS) which has proven to be effective, and the next step is to prove its safety.Methods: Preterm birth (PTB) and low birthweight (LBW) of 176 singletons born after using the SCS, 105… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…We recently reported a favourable perinatal outcome for SCS singletons born after fresh embryo transfer when compared to singletons born after conventional IVF in Belgium [22]. The low prevalence of PTB and LBW we observed after using SCS prompted us to initiate a study to compare our results with a large cohort of naturally conceived newborns.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We recently reported a favourable perinatal outcome for SCS singletons born after fresh embryo transfer when compared to singletons born after conventional IVF in Belgium [22]. The low prevalence of PTB and LBW we observed after using SCS prompted us to initiate a study to compare our results with a large cohort of naturally conceived newborns.…”
Section: Discussionmentioning
confidence: 88%
“…In a recent report and making use of BELRAP data (Belgian Register for Assisted Procreation), we found that for babies born after a fresh embryo transfer (ET), the prevalence of PTB and LBW was significantly lower in SCS singletons when compared to all singletons born after conventional IVF in Belgium during the same study period [22]. Because of this unexpected finding, we decided to compare our SCS singletons with naturally conceived singletons.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of LCIVF is to make in vitro fertilization (IVF) safe, affordable, efficient, and accessible to infertile couples living in resource-constrained nations. For this, Ombelet et al [ 39 , 40 ] created the simplified low-cost IVF culture system. Similar to traditional intracytoplasmic sperm injection (ICSI), this cutting-edge low-cost IVF method produces outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of opportunities to improve the current situation. Among them are health education and lifestyle improvement programs to prevent disease and thus reduce the need for MAR, one-stop clinics for infertility investigations, and the use of alternative treatments for mild and moderate male infertility, such as soft stimulation protocols and low-cost IVF laboratories ( Ombelet et al , 2022 , 2023 ). However, many other challenges remain, such as persistent unhealthy lifestyle, environmental pollutants, socio-cultural, and religious barriers for some modalities of male infertility treatment, the high cost of MAR medications, scarcity of MAR centers in the public sector, lack of coverage of infertility treatment by health insurance policies, and lack of economic support by international agencies and philanthropies to support infertility treatment in Africa.…”
Section: Mrh: a Global Perspectivementioning
confidence: 99%